EGGS AND EGGSHELLS OF CROCODYLOMORPHA FROM THE LATE JURASSIC OF PORTUGAL - Russo, João (2014)
The Lourinha Formation, cropping out on the western shore of Portugal, dated from the Late Kimmeridgian to latest Tithonian-earliest Berriasian, has produced an extensive record of fossil vertebrates, including nine localities with nests, eggs and embryos. In four of these localities, Paimogo N and S, Casal da Rola and Peralta, associated with dinosaur egg material, several thinner eggshell fragments were recovered. Besides the fragments, 3 partial eggs were found. In a fifth locality, in Cambelas, a nest with 13 mostly well preserved eggs was recovered. In average, these eggs are 42 mm long and 26 mm wide. A preliminary observation suggested a crocodilian affiliation based on eggshell features such as tabular ultrastructure, wedge-shaped shell units and triangular blocky extinction. We found that, excluding the small nest, all the samples exhibit a clear, outer diagenetic layer (DL) with recrystallized and secondary calcite. The typical crocodiloid ultrastructure and shell units are present, although faint and not always clearly defined; strong sub-horizontal fracturing precludes a more extensive description. No ultrastructure is observable in the nest sample. The presence of basal plate group knobs on the inner eggshell surface are also diagnostic. Three layers can be differentiated in three of the samples, with an inner or mammillary layer corresponding to the dark basal knobs, a medium layer characterized by the presence of the tabular ultrastructure, and an outer layer, below the DL, distinguishable from the medium layer by a darker thin band. Furthermore, all the samples show the distinct triangular blocky alternating extinction. The thicknesses range between 163 μm and 392 μm, which is consistent with values for fossil crocodiloid eggshells. The density of the mammillae is very similar to what is observable in extant eggshells, as are the pores, with long, straight canals. Moreover, the ellipsoid shape of the eggs is typically crocodilian, even though such shape is shared with some dinosaur eggs. Thus, this analysis allows us to ascribe it to the oofamily Krokolithidae, making it the oldest crocodylomorph eggs known so far, as well as the best record for eggs of non-crocodylian crocodylomorphs. Based on the morphological characters, we tentatively assign it to the oogenus Krokolithes. The structure of crocodilian eggshells is very conservative and has seemingly remained unchanged since at least the Late Jurassic.